Categorizing the barriers in adopting sustainable supply chain initiatives: A way-forward towards business excellence - Muhammad Nazam; Muhammad Hashim; Sajjad Ahmad Baig; Muhammad Abrar; Hakeem Ur Rehman; Muhammad Nazim; Ali Raza (Cogent Business & Management, 2020)
Sustainable supply chain initiatives (SSCI) increasingly attract the interest of industrialists, policy makers and academia in achieving business excellence. There is a tremendous pressure from stakeholders to adopt sustainable supply chain practices in manufacturing of hygienic products. Agro-based industries in emerging economies like Pakistan are at initial stage in tackling with many barriers to implement (SSCI). The purpose of this study is to categorise the barriers and formulate a multi-criteria decision-making (MCDM) framework based on fuzzy analytical hierarchy process (FAHP) which effectively handles the subjectivity and complexity of experts' inputs. The top seven barriers regarding the implementation of (SSCI) in this study were identified namely: (1) lack of sustainable outsourcing, (2) lack of sustainable production and distribution, (3) fear and resistance towards sustainable competitiveness and innovation, (4) trust deficit on sustainable buyer-supplier relationship, (5) lack of sustainable marketing and organizational culture, (6) difficulty in sustainable knowledge sharing (7) complexity in adopting sustainable technology practices. The key findings highlight that lack of sustainable outsourcing factor is key barrier for adopting (SSCI). Finally, the sensitivity analysis is applied to confirm the suitability among the ranked barriers. The outcome of this research would be supportive measures for the stakeholders by providing insights on barriers to implement (SSCI) concept for achieving sustainable development goals in line towards business excellence.
Keywords: 650; supply chain initiatives; barriers; fuzzy AHP